The Effectiveness of Puppet Play Therapy on Social Skills of Children with Cochlear Implantation - Sedigheh Rezaei Dehnavi (Journal of Rehabilitation Sciences and Research, 2025)
Background: Learning social skills presents a significant challenge for Hearing Impaired Children (HIC). Play therapy is a recommended intervention to facilitate and accelerate social-emotional development. This study aimed to evaluate the effectiveness of Puppet Play Therapy (PPT) on the social skills of male children aged 6 to 9 years with Cochlear Implants (CI).Methods: This quasi-experimental study utilized a pretest-posttest design with a control group. A total of 24 male students aged 6 to 9 years with CI were randomly assigned to the experimental (n=12) and control (n=12) groups. Theexperimental group received cognitive-behavioral play therapy using puppets in ten 45–60-minute sessions. Social skills were assessed using the Gersham and Eliot Social Skills Rating System during the pretest and posttest.Results: The findings indicated that the mean scores of three social skills subscales, including cooperation (P<0.001), assertion (P<0.001), and selfcontrol (P<0.001), were significantly higher in the experimental group after receiving PPT.Conclusion: The results suggest that Puppet Play Therapy is an effective intervention for enhancing social skills in children with CI, and it can serve as a valuable supplementary rehabilitation approach.